Inhaled nebulised medications in palliative care - a survey among palliative care practitioners in Germany - Ruth Mair; Annette Schnell; Christine Steger-Arand; Wolfgang Herr; Michael Rechenmacher (BMC Palliative Care)
Abstract Background In palliative care, alternative routes for drug application besides the oral and intravenous administration are frequently necessary. Up-to-date, very little is known about the familiarity, use and perceived relevance of inhalative medications for symptom control among palliative care practitioners. Methods We conducted an anonymous online survey among palliative care physicians throughout Germany between 09/2021 and 04/2022. The questionnaire covered participants’ sociodemographics, as well as familiarity, perceived relevance and prescription practices regarding 21 nebulised drugs. Analysis was performed using methods of descriptive statistics. Results 108 fully completed questionnaires were analysed. Most of the participants were employed in palliative care for 5 + years. The administration of normal saline, mucoactive drugs, bronchodilators and steroids via nebulisation was a widely known and frequently used technique among the participants, as evidenced by its regular use in clinical routine. About 50% of the participants reported to know epinephrine and tranexamic acid for anti-oedematous or haemostyptic effects, respectively. Both drugs were considered “relevant” by more than 60% of the prescribers. Only a minority of participants reported to know and use nebulised opioids, iloprost, several antibiotics, heparin, ketamine and lidocaine. Conclusions Our survey shows that nebulised drugs are prescribed and considered relevant in palliative care. However, for several of the mentioned medications only limited data is available regarding use and effectivity. There is also uncertainty to what extent the existing data may be transferable into routine palliative care setting. Therefore, more evidence should be generated. Trial registration Not applicable.